THE GLOBAL TECTONIC PATTERN - Doglioni C. (My University, 1990)
The relative motion vectors between the lithosphere and the underlying mantle appear to follow global flow lines which can be constructed by linking axes of extension and compression over the Earth's surface. The flow lines for the last 40 Ma are generally WNW-ESE (E-W), with an undulation of an about 15,000 km wavelength, showing a gradual and progressive variation in orientation. The undulation, which is sharper to the east, may reflect the mantle flow around an unstable rotation axis. The westward motion of the lithospheric plates could be interpreted as a result of differential angular velocity induced by the deceleration of the earth's rotation or, in a toroidal field, by the effects induced by lateral heterogeneities both in the lithosphere and in the mantle. In this light, plate tectonics is a consequence of variable decoupling at the base of the lithosphere as a function of mantle anisotropies. Simply stated, when there is compression or transpression between two plates, it is the eastern plate which moves more rapidly westwards relative to the underlying mantle. If there is extension or transtension, it is the western plate that moves faster westwards. Lithospheric subduction, especially if it dips westward, produces an obstacle to the eastward flow of the mantle. This is referred to as the Nail Effect. The eastward roll-back of the subduction hinge due to the mantle push will generate back-arc extension. Subductions following the mantle flow (E or NE-dipping) are associated to thicker thrust belts with huge exposures of basement rocks in the hinterland and shallow foreland basins. The subductions contrasting the mantle flow (W or SW-dipping) are characterized by shallow thrust belts with deep foreland basin and coeval extension in the back. E-dipping subductions are passive responses to actively thrusting plates: the base plate and intra-lithospheric decollements are connected to the surface and can uplift deep rocks. The W-dipping subductions are enhanced by the eastward mantle flow: the base plate detachments are folded, subducted themselves and nerver connected to the surface, and only superficial detachments occur at the plate boundaries. First-order tectonic features appear to be perpendicular or slightly oblique to the global flow lines. Second-order tectonic features are related to localized rotations of plates. The model is applied to the Mediterranean area, where there are several observations that are not easily explicable in terms of standard plate-tectonic processes: the eastward or northeastward relative migration of the underlying mantle with respect to an inhomogeneous disrupted lithosphere could explain the tectonic evolution of this area.